2020
DOI: 10.1002/tox.22899
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 attenuates the osimertinib resistance by reducing the stemness of non‐small cell lung cancer cells

Abstract: In the present study, we found that Ginsenoside Rg3 attenuated the stemness of non-small cell lung cancer (NSCLC) cells, evident by decreasing spheroid formation ability, ALDH1 activity and stemness marker expression. Furthermore, osimertinibresistant NSCLC cells displayed a stronger stemness than the parental cells.Ginsenoside Rg3 reduced the stemness and osimertinib resistance of osimertinibresistant cells. RNA-sequencing revealed that Hippo signaling was shown on the top of the most upregulated pathways reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Collectively, Rg3 could sensitize hypoxic lung cancer cells to DDP through preventing NF-κB induced EMT and stemness. Also, Rg3 (Tan et al, 2020) could target CSCs and reverse osimertinib resistance in H1975 and H1975/OR cells by activating the Hippo pathway, which was key cancer signaling in association with cell proliferation, cell death, and cancer metastasis (Kulkarni et al, 2020). Co-treatment of Rg3 and osimertinib could promote expressions of the active components of the Hippo pathway, such as MST1/2 and LATS1/2, and depress the expression of the negative executor or effector.…”
Section: Modulating Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…Collectively, Rg3 could sensitize hypoxic lung cancer cells to DDP through preventing NF-κB induced EMT and stemness. Also, Rg3 (Tan et al, 2020) could target CSCs and reverse osimertinib resistance in H1975 and H1975/OR cells by activating the Hippo pathway, which was key cancer signaling in association with cell proliferation, cell death, and cancer metastasis (Kulkarni et al, 2020). Co-treatment of Rg3 and osimertinib could promote expressions of the active components of the Hippo pathway, such as MST1/2 and LATS1/2, and depress the expression of the negative executor or effector.…”
Section: Modulating Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…For example, BST204, a fermented ginseng extract containing high quantities of Rh2 and Rg3, strongly suppressed cancer stemness of embryonic carcinoma cells by downregulating stemness markers and transcription factors at both transcriptional and protein expression levels ( Park et al, 2020 ). Meanwhile, ginsenoside Rg3 was also shown to decrease tumor CSC sphere-forming capacity that led to deregulated expression of stemness-related markers and attenuated CSC tumorigenic activities in several types of cancer ( Wang et al, 2018 ; Phi et al, 2019a ; Oh et al, 2019 ; Tan et al, 2020 ). Moreover, it has been reported that ginsenoside Rd may downregulate levels of genes related to stemness and EMT by binding to epidermal growth factor receptor (EGFR) ( Phi et al, 2019b ).…”
Section: Ginseng Could Inhibit Stemness Of Cancer Stem Cellsmentioning
confidence: 99%
“…A recent study revealed that osimertinib-resistant NSCLC cells displayed stronger stemness than the parental cells, which conferred to them greater metastatic potential (55). Notably, ginsenoside Rg3 attenuates the stemness of NSCLC cells and the resistance to osimertinib, as evidenced by the decreased expression of stemness markers and decreased spheroid formation ability, which is dependent on the Hippo signaling pathway (56). Furthermore, ginsenosides overcome resistance to chemotherapy drugs such as cisplatin (DDP), which is used for the treatment of NSCLC.…”
Section: Saponinsmentioning
confidence: 99%